PERAN INFORMASI MODAL INTELEKTUAL SEBAGAI VARIABEL MODERASI PADA HUBUNGAN ANTARA MODAL INTELEKTUAL DAN NILAI PERUSAHAAN - Saring Suhendro; Usep Syaipudin; Mega Metalia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This paper empirically examines whether type of intellectual capital (IC) information affect market value of the firm. This paper also examines whether voluntary disclosure of intellectual capital information will strengthen the affect of intellectual capital information to market value of the firm. The samples were the banking industry firm listed on the Indonesia Stock Exchange from 2017-2019. The variable of type of IC information measured by Intellectual Capital Disclosure Index (ICDI) by modifying the approach of García-Meca and Martínez (2007). The study finds that IC positively effect on market value of the firms. Moreover, this study finds that IC information-especially voluntary disclosure also strengthen (as moderating variable) the IC effect on firm value.